2017
DOI: 10.1002/ps.4518
|View full text |Cite
|
Sign up to set email alerts
|

Inductions of reproduction and population growth in the generalist predator Cyrtorhinus lividipennis (Hemiptera: Miridae) exposed to sub‐lethal concentrations of insecticides

Abstract: Sub-lethal concentrations of triazophos, deltamethrin and imidacloprid stimulated reproduction and enhanced population growth of C. lividipennis. The reproductive stimulation might result from the up-regulation of ClVg or ClSPATA13. These findings may be useful in mediating populations of planthoppers. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…In BPH, Vg mRNA expression was increased by triazophos . In Cyrtorhinus lividipennis , Vg mRNA expression was also induced by triazophos . Although LC 20 to LC 40 of triazophos all significantly increased the expression level of LsVg , LC 30 induced the highest expression.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In BPH, Vg mRNA expression was increased by triazophos . In Cyrtorhinus lividipennis , Vg mRNA expression was also induced by triazophos . Although LC 20 to LC 40 of triazophos all significantly increased the expression level of LsVg , LC 30 induced the highest expression.…”
Section: Discussionmentioning
confidence: 91%
“…23,25,[28][29][30] In Cyrtorhinus lividipennis, Vg mRNA expression was also induced by triazophos. 58 Although LC 20 to LC 40 of triazophos all significantly increased the expression level of LsVg, LC 30 induced the highest expression. Interestingly, the trend of the expression of LsVg induced by different doses of triazophos was consistent with RSV vertical transmission rates, suggesting that triazophos-induced RSV transmission in SBPH may be correlated with LsVg.…”
Section: Wileyonlinelibrarycom/journal/psmentioning
confidence: 92%
“…On the other hand, Joshi et al (1982) reported that neem seed kernel extracts increased the fecundity of the egg parasitoid, Telenomus remus (Hymenoptera: Platygastridae). We recently reported that the fecundity of C. lividipennis could be induced by sublethal concentrations of triazophos, deltamethrin and imidacloprid (Lu et al 2017). Further studies are needed to explore the mechanism and ecological outcome of insecticide-induced reproduction in C. lividipennis.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory cultures of C. lividipennis were originally collected from rice fields in Yangzhou (32°23´N, 119°26´E). N. lugens and C. lividipennis were reared on II-You 118 as described by Lu et al (2017). Rice plants and insects were maintained in a growth chamber at (28±2)°C with a 14:10 h (light:dark) photoperiod and 70-80% RH.…”
Section: Rice Insects and Insecticidesmentioning
confidence: 99%
“…Both transcription and protein levels of Vg and VgR were down-regulated by bacterial infection in Apis mellifera (Hymenoptera: Apidae) ( Abbo et al, 2017 ). Intriguingly, the expression of Vgs is dynamic and varies after exposure to different insecticides; e.g., Vg was decreased in a chlorpyrifos-resistant strain and identified as a novel potential resistance-related protein in Frankliniella occidentalis (Thysanoptera: Thripidae), while a drastic increase in the abundance of Vg was observed after exposure of sublethal concentrations of triazophos and deltamethrin in Cyrtorhinus lividipennis Ruter (Hemiptera: Miridae) ( Yan et al, 2015 ; Lu et al, 2017 ). Hence, the identification and characterization of Vg and VgR, as well as the determination of their expression after exposure to sublethal doses of different insecticides, need to be established in each species to better understand the molecular mechanism of the sublethal effects of insecticides on reproduction in insects.…”
Section: Introductionmentioning
confidence: 99%